Ondansetron in the Prevention of Post Cardiotomy Delirium after Coronary Artery Bypass Grafting Surgery - Kamal, Daniyal Ahmad; Iqbal, Muhammad Afsheen; Sarfraz, Sana; Nawaz, Atif; Ali, Nasir; Masroor, Rehan; Rehman, Fahad Ur; Sana, Ayesha (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the efficacy of Ondansetron as a prophylctic agent in patients undergoing Coronary Artery Bypass Grafting. Study Design: Quasi-experimental study. Place and Duration of study: Adult Cardiac Surgery Department, AFIC/NIHD Rawalpindi Pakistan, from Nov 2022 to Feb 2023. Methodology: A total of 156 patients undergoing Coronary Artery Bypass Grafting Surgery irrespective of age and gender were included in the study via nonprobability consecutive sampling. Patients who had a previous history of psychiatric illness, and those in whom delirium could not be reliably tested were excluded from the study. The study population was divided into two groups (group A and group B). Those in the group A received 8mg Ondansetron intravenously on zero, first and second post-operative day. Group B did not receive any intervention. Descriptive statistics were used to measure percentages, frequencies and Mean±SD. Comparison between variables was made by Chi-square test for categorical variables and t-test for continuous variables. p<0.05 was considered statistically significant. Results: Total 156 patients were included in the study and mean age of the patients was 59.47±10.98 years. A total of 3(14.3%) patients who had been given Ondansetron compared to 18(85.7%) patients who were not given Ondansetron developed delirium (p<0.001). Other factors significantly associated with post cardiotomy delirium were age (p<0.001), hypertension (p<0.001), and diabetes (p=0.03). Conclusion: Our study revealed that Ondansetron can be used effectively to reduce the incidence of post cardiotomy delirium in patients of coronary artery bypass grafting.